The Effects of Aromatherapy on Sleep Quality in Diabetes Patients with Restless Leg Syndrome in Taiwan - Pei-Jung Yu; Ai-Fu Chiou (European Scientific Journal, ESJ, 2018)
This study is a longitudinal experimental design that examine the effects of aromatherapy on sleep quality in diabetes patients with restless leg syndrome (RLS). Patients in the experimental group received the aromatherapy intervention for 6 weeks, while those in the control group received only regular nursing care. The instruments included Pittsburg Sleep Quality Index and SureStep TM of blood glucose meters. Data were collected at pre-test, 2nd week, 4th week, and 6th week after the aromatherapy. Data analysis included descriptive analysis, chi-square, independent t test, Pearson correlation, repeated measure ANOVA and general linear mixed-effect models. Forty-four diabetes patients with RLS were randomly assigned to the experimental group (n=22) and the control group (n=22) at a hospital in northern Taiwan. Sleep quality of diabetes patients with RLS was poor in this study. Sleep latency of patients in the experimental group was improved at 2nd week after aromatherapy. Subjective sleep quality and sleep disturbance of patients was also improved at 4th week after aromatherapy. At 6th week, patients in the experimental group had increased their sleep duration, and improved their overall sleep quality. The level of blood sugar was decreased at 2nd week after aromatherapy on experimental group. Based on the analysis it was concluded that Aromatherapy can ameliorate both blood sugar and sleep quality of diabetes patients with RLS. Thus aromatherapy can be a safe, noninvasive, effective approach for clinical nurses as a therapy in routine care to improve sleep quality in diabetes patients with neuropathy.